2021
DOI: 10.21203/rs.3.rs-932780/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of processed quinoa on performance traits, small intestinal morphology, and blood parameters of Ross broiler chickens

Abstract: Restrictions on access to important components of poultry rations such as corn and soybean meal are among the biggest issues in the poultry feed industry. Quinoa with a very high nutritional value can be a good alternative. The present study aimed to investigate the effect of processed quinoa seeds on performance, small intestinal morphology, and blood parameters of Ross broiler chickens. The present experiment was performed with 5 treatments, 4 replications, and 15 chickens per pen in a completely randomized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…These compounds are anti-nutrition factors because they reduce the ability to digest, which negatively affects the performance of impeding the growth performance of birds (Liu et al 2020a). Therefore, soaking contributed to the disposal of these inhibitors, as one study stated that treatment of quinoa seeds can reduce the negative effect of anti-nutrient factors and improve the morphological characteristics of broilers (Zeyghami et al, 2021). The reason for the increase in the feed consumption in favor of treatments to which percentages of raw and treated quinoa seeds are added compared to the control treatment may be due to the phenolic compounds that the quinoa seeds contain, which would smell aromatic and open the appetite, and thus the birds' appetite for eating larger quantities of feed (Christaki et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These compounds are anti-nutrition factors because they reduce the ability to digest, which negatively affects the performance of impeding the growth performance of birds (Liu et al 2020a). Therefore, soaking contributed to the disposal of these inhibitors, as one study stated that treatment of quinoa seeds can reduce the negative effect of anti-nutrient factors and improve the morphological characteristics of broilers (Zeyghami et al, 2021). The reason for the increase in the feed consumption in favor of treatments to which percentages of raw and treated quinoa seeds are added compared to the control treatment may be due to the phenolic compounds that the quinoa seeds contain, which would smell aromatic and open the appetite, and thus the birds' appetite for eating larger quantities of feed (Christaki et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…However, the containment of the outer shell of the seeds on some anti-nutritional substances in small proportions, the most important of which are saponins, phytic acid, and trypsin inhibitors, poses a fear of using raw quinoa seeds. It may affect the metabolism process by reducing the utilization of protein and digesting it well, as well as reducing appetite, destroying intestinal villi, and inhibiting the Immunofluorescence system in poultry, especially young birds (Zeyghami et al, 2021). Therefore, studies indicated preparatory treatments to contribute to increasing the use and benefit of the seeds, improving the nutritional value more, eliminating harmful nutritional inhibitors and the taste of soaking seeds.…”
Section: Introductionmentioning
confidence: 99%
“…These facts encourage the use of these seeds as one of the components of the broiler's diet, The outer shell of the seeds contains some anti-nutritional substances in small proportions, the most important of which are saponins, phytic acid, and trypsin inhibitors, which pose a concern with the use of raw quinoa seeds, which may affect the metabolism process by reducing the utilization of protein and its good digestion, as well as reducing appetite, destroying intestinal villi and inhibiting the immune system in poultry. Especially young birds [11] .Therefore, studies indicated preparatory treatments to contribute to increasing the use and benefit of the seeds, improving the nutritional value more, eliminating harmful nutritional inhibitors and the taste of soaking seeds. Plus, the contribution of soaking to the germination process, leads to a high level of protein as well as phenolic compounds and vitamins and an increase in the bioavailability of amino acids inside the seeds [12].…”
Section: Introductionmentioning
confidence: 99%